2011
DOI: 10.1371/journal.pone.0027645
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Warming and Nitrogen Addition on Soil Nitrogen Cycling in a Temperate Grassland, Northeastern China

Abstract: BackgroundBoth climate warming and atmospheric nitrogen (N) deposition are predicted to affect soil N cycling in terrestrial biomes over the next century. However, the interactive effects of warming and N deposition on soil N mineralization in temperate grasslands are poorly understood.Methodology/Principal FindingsA field manipulation experiment was conducted to examine the effects of warming and N addition on soil N cycling in a temperate grassland of northeastern China from 2007 to 2009. Soil samples were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 42 publications
5
32
1
1
Order By: Relevance
“…This finding is consistent with results of previous studies in wetland and paddy soils [17], [33], [34], [37]. The reason for the significant effect of incubation temperature on N mineralization in this study ( P <0.01, Table 2) was that because temperature could greatly affect soil microbial processes [6], [10], [16], [29], [39] and higher temperature favored microbial and enzyme activity [2], [40] and thus enhanced N mineralization processes. In contrast, lower temperatures (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with results of previous studies in wetland and paddy soils [17], [33], [34], [37]. The reason for the significant effect of incubation temperature on N mineralization in this study ( P <0.01, Table 2) was that because temperature could greatly affect soil microbial processes [6], [10], [16], [29], [39] and higher temperature favored microbial and enzyme activity [2], [40] and thus enhanced N mineralization processes. In contrast, lower temperatures (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Both soil organic C and N are mineralized to simple inorganic forms by a highly dynamic community of microbial decomposers (Paul, 2007;Manzoni and Porporato, 2009). SOM mineralization results in a gross release of CO 2 to the atmosphere and provides most of the inorganic nutrient necessary for plant and microbial growth (Manzoni and Porporato, 2009;Xia et al, 2009;Ma et al, 2011). Therefore, soil C and N mineralization have important roles in the functioning of soil in nutrient cycling, structural formation and plant interactions (Wardle et al, 2004;Harris et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Under the N and P addition, soil moisture was significantly correlated with net mineralization and nitrification rate, which suggested that it was one of the dominant factors affecting N. Net N mineralization and nitrification rate under N fertilization was significantly correlated with environmental factors (soil organic C, soil C/N and soil total N). Soil N mineralization was not positively correlated with the soil microbial biomass N or C. Key words temperate grassland; N and P additions; nitrogen mineralization; soil inorganic N; affecting factor (Holst et al, 2007;Müller et al, 2007), 并受到生物与非生物 因子(如土壤温度、湿度、有机质及微生物群落结构 等)的影响 (Zaman & Chang, 2004;Liu et al, 2010) Jussy et al, 2004;Wang et al, 2014;Ma et al, 2011) …”
Section: Introductionmentioning
confidence: 99%
“…Other than in the control, 1 g P 2 O 5 ·m -2 ·a -1 is added to each treatment in the N addition experiment, and 2 g N·m -2 ·a -1 is added to each treatment in the P addition experiment. 机质、温度及土壤水分有效性等最为重要 (Chapin et al, 2002;Zaman & Chang, 2004;Liu et al, 2010;Ma et al, 2011)。氮添加情景下的净矿化、硝化速率与 土壤有机碳和土壤全氮之间呈显著的正相关关系, 表明了土壤有机碳及全氮的增加对草地土壤矿化及 硝化作用都具有明显的促进效应 (Hacin et al, 2001;Wang et al, 2008;。土壤中较高的 有机碳和全氮含量提高了微生物的活性, 进而促进 了氮素矿化速率 (Berendse, 1990;Kitayama, 1996;Sanchez et al, 1997)。净矿化及硝化速率与土壤C/N 之间呈显著的负相关关系, 进一步反映了氮添加会 降低温带典型草原土壤的C/N, 引起碳的有效性减 少及微生物对N需求的下降, 从而促进了土壤净氮 矿化速率 (Hart et al, 1994;Vourlitis & Zorba, 2007;Ma et al, 2011)。土壤微生物量氮、碳与净矿化和硝 化速率之间并不存在显著的相关性, 以往的研究也 得出类似的结果 (Holems & Zak, 1994;Hossain et al, 1995;Bengtsson et al, 2003;傅民杰等, 2009) …”
Section: Introductionunclassified